An Investigation of Health and Safety Measures in a Hydroelectric Power Plant - Amevi Acakpovi; Lucky Dzamikumah (Safety and Health at Work, 2016)
Background: Occupational risk management is known as a catalyst in generating superior returns for all stakeholders on a sustainable basis. A number of companies in Ghana implemented health and safety measures adopted from international companies to ensure the safety of their employees. However, there exist great threats to employees' safety in these companies. The purpose of this paper is to investigate the level of compliance of Occupational Health and Safety management systems and standards set by international and local legislation in power producing companies in Ghana. Methods: The methodology is conducted by administering questionnaires and in-depth interviews as measuring instruments. A random sampling technique was applied to 60 respondents; only 50 respondents returned their responses. The questionnaire was developed from a literature review and contained questions and items relevant to the initial research problem. A factor analysis was also carried out to investigate the influence of some variables on safety in general. Results: Results showed that the significant factors that influence the safety of employees at the hydroelectric power plant stations are: lack of training and supervision, non-observance of safe work procedures, lack of management commitment, and lack of periodical check on machine operations. The study pointed out the safety loopholes and therefore helped improve the health and safety measures of employees in the selected company by providing effective recommendations. Conclusion: The implementation of the proposed recommendations in this paper, would lead to the prevention of work-related injuries and illnesses of employees as well as property damage and incidents in hydroelectric power plants. The recommendations may equally be considered as benchmark for the Safety and Health Management System with international standards.